The Cybersecurity Risk. (Communications of the ACM, 2012)
The article discusses cybersecurity and computer-related risks. Topics include how to prevent computer hacking issues, the amount of money spent on computer security research and security program development worldwide, and data theft of sensitive information. Information is provided on the various techniques that computer hackers can use to breach computer security barriers, which includes supply-chain insertion and the breach of authentication layers. It is noted that there is no single solution that addresses the problem of computer security breaches.